2012
DOI: 10.1016/j.jacc.2011.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictive Factors, and Prognostic Value of New-Onset Atrial Fibrillation Following Transcatheter Aortic Valve Implantation

Abstract: NOAF occurred in about one-third of the patients with no prior history of AF undergoing TAVI and its incidence was increased in patients with larger LA size and those undergoing transapical TAVI. NOAF was associated with a higher rate of stroke/systemic embolism, but not a higher mortality, at 30 days and at 1-year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(79 citation statements)
references
References 31 publications
(41 reference statements)
6
62
1
5
Order By: Relevance
“…AF had not been considered a significant risk for TAVR patients in the past. 247 However, findings from the study reported by AmatSantos et al 209 suggest that the incidence of newonset AF may be high in the first 30 days after TAVR. They studied 138 consecutive patients with no history of AF who had TAVR and were moni tored until hospital discharge.…”
Section: Transcatheter Structural Interventionsmentioning
confidence: 98%
See 2 more Smart Citations
“…AF had not been considered a significant risk for TAVR patients in the past. 247 However, findings from the study reported by AmatSantos et al 209 suggest that the incidence of newonset AF may be high in the first 30 days after TAVR. They studied 138 consecutive patients with no history of AF who had TAVR and were moni tored until hospital discharge.…”
Section: Transcatheter Structural Interventionsmentioning
confidence: 98%
“…AF is a common arrhythmia after any type of cardiac sur gery, including CABG surgery or surgical valve replace ment/repair. [204][205][206][207][208][209] Newonset AF in CABG may occur at any point from the time of the procedure, usually 2 to 4 days postoperatively with peak occurrence at 2 days. 206 AF occurs in 28% to 33% of patients undergo ing CABG.…”
Section: Major Cardiac Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic AF are at significantly higher risk for late stroke post-TAVR [30]. In contrast, patients who present with new onset AF (intraprocedurally or within 24 h of TAVR) are more likely to experience a stroke or systemic embolism within 30 days post-TAVR [31]. Predictors of new onset AF include increased left atrial size and transapical approach [31]; it is unknown whether the additional early risk of embolism could be reduced with antiarrhythmic or anticoagulation therapies in this sub-population [32].…”
Section: Discussionmentioning
confidence: 99%
“…AF has been reported in more than 30% of the patients considered for TAVR and is associated with a markedly increased risk of mortality and thromboembolic events after valve replacement [6,7]. In addition, new onset AF was observed in one third of the patients undergoing continuous electrocardiographic (ECG)-monitoring after TAVR and associated with higher rates of postprocedural embolic events [8]. Identifying the appropriate anticoagulation strategy after TAVR remains an important clinical challenge that has resulted in a large variability of antithrombotic therapies, ranging from triple therapy (DAPT + oral anticoagulation [OAC]) to vitamin-K antagonists (VKA) alone [9].…”
Section: Introductionmentioning
confidence: 99%